Paleo slow cooking / Molly Pearl - Pearl, Molly
The wildly popular Paleo Diet is based on eating like our stone-age ancestors -- good fats, lean meats, and lots of fruits and vegetables. "Idiot's Guides: Paleo Slow Cooking" takes a fabulous diet and brings it together with the trusty, time-saving slow cooker cooking method. More than 85 fantastic recipes and beautiful, full-color photography help readers satisfy a Paleo-friendly diet, while saving time and prep work.